Doctoral theses on museology in Spanish universities: a bibliometric analysis, 1986-2018 - Mochón-Bezares, Gonzalo; Sorli-Rojo, Ángela (Revista General de Información y Documentación, 2020)
The present work performs a bibliometric analysis of the production of doctoral theses on museology defended in Spanish universities between 1986 and 2018, and collected in the TESEO database of the Ministry of Education and Professional Training. The total number of theses recovered is 248. The evolution of thesis production has been reviewed based on the years of defense, the writing languages, the reading universities, the subject and the doctors in charge of directing, as well as the information on the members of the evaluating courts. It is concluded that the number of theses on museology has increased considerably in recent years, highlighting the dispersion of production by universities, a high thematic concentration around the History of Art and Education, a high distribution among thesis directors and high degree of transience among members of the courts.